Conventional and underwater friction stir welded AA2024-T351 aluminium alloy – a comparative analysis. (24th September 2020) - Balaji, Swathi; B., Sujay Aadithya; K., Balachandar
Abstract : Purpose: Friction stir welding (FSW) and underwater friction stir welding (UWFSW) of aluminium alloy 2024-T351 was carried out, with a chosen set of parameters, namely, rotational speed of 450 rpm, 560 rpm and 710 rpm, welding speed of 25 mm/min, 40 mm/min and 63 mm/min and tool tilt angle of 0º, 1° and 2º. This study aims to understand the correlation between temperatures and weld parameters, finite element simulation was carried out using Abaqus®. Design/methodology/approach: Comparative analysis of the mechanical properties of the samples welded with FSW and UWFSW was carried out and correlated with that of the microstructures. Microhardness survey was also conducted across the weldments to support the findings. Findings: Samples welded with higher rotational speed and low traverse speed favoured good quality, defect-free welds with enhanced material flow. Underwater welded samples resulted in improved mechanical properties than that of the samples welded with conventional FSW. Higher cooling rates resulted in finer grains in all UWFSW samples than that of conventional FSW samples, which, in turn, also reflected in the microhardness survey done across the weldments. Among the chosen window of the parameter, samples welded with 710 rpm, 25 mm/min and 2° had shown improvement in mechanical properties. Research limitations/implications: This work was carried out in a milling machine, which limits the rotational speed which could be used. Optimistically, this limitation also paves way for using the commonly available milling to be used for FSW. Originality/value: This original research study shall open opportunities to enable FSW and UWFSW to be done on similar/dissimilar joints of varying composition. Additionally, this research study throws enough light on the age – hardenable aluminium alloy being welded in a commonly available milling machine.